A novel and modified fluorescent amphiphilic block copolymer simultaneously targeting to lysosomes and lipid droplets for cell imaging with large Stokes shift. (5th March 2022) - Zhang, Zhi-Hao; Li, Cong-Cong; Cui, Wei-Long; Qu, Jianbo; Zhang, Haitao; Liu, Keyin; Zhu, Xiu-Zhong; Wang, Jian-Yong
Graphical abstract: In this paper, we designed and synthesized a novel 1, 8-naphthalimide-based fluorescent monomer which can target to lysosomes and LDs simultaneously. The fluorescent monomer was applied to copolymerize with a hydrophilic material PEGMA300 by reversible addition-fragmentation chain transfer polymerization (RAFT) for construction of fluorescent amphiphilic block copolymer Poly (Nap-Lyso-MMA- co -PEGMA300 ) for the first time, which exhibited good water solubility and photostability, large Stokes shift (almost 130 nm), good selectivity, low cytotoxicity, and wide pH stability. Furthermore, it was sensitive to the solvent polarity and lipo-solubility. We successfully achieved a series of bio-imaging applications such as cell imaging, lysosome-LDs dual-locating imaging. These results indicated that the fluorescent copolymer possessed the remarkable bio-membrane penetration, lysosomes-targeting with the Pearson's Correlation of 0.832443, LDs-specificity with the Pearson's Correlation of 0.938595. Interestingly, fluorescent polymer could locate in dual- organelles simultaneously with different fluorescence signal, which could distinguish by the dot-fluorescence in LDs and the sheet-fluorescence in Lysosomes, accompanied by the brighter fluorescence in LDs than in Lysosomes. Based on these good properties as mentioned above, we expect the synthetic fluorescent polyacrylate could serve as a promised candidate to understand the interplay between lysosomes and LDs for promoting progress in biomedical fields. Highlights: The fluorescent amphiphilic block copolymer Poly (Nap-Lyso-MMA- co -PEGMA300 ) was firstly designed and synthesized for locating in lysosomes and LDs in living cells. The fluorescent amphiphilic block copolymer Poly (Nap-Lyso-MMA- co -PEGMA300 ) exhibited good water solubility, low cytotoxicity, large Stokes shift (almost 130 nm), desirable photostability, good selectivity and wide pH stability. Poly (Nap-Lyso-MMA- co -PEGMA300 ) was sensitive to the solvent polarity and lipo-solubility. The fluorescent polymer possessed the remarkable bio-membrane penetration, lysosomes-targeting with the Pearson's Correlation of 0.832443, LDs-specificity with the Pearson's Correlation of 0.908438. The fluorescent polymer was also located in LDs and lysosomes imaging simultaneously in living HeLa cells with Pearson's Correlation of 0.799811. Abstract: Lipid droplets (LDs) and lysosomes are vital subcellular organelles which exist in almost all eukaryotic cells and play important roles in various physiological activities. In addition, recent studies showed that the interplay between LDs and lysosomes was related to metabolic diseases. Therefore, it is particularly meaningful for the medical field to develop an effective strategy to monitor lysosomes and LDs simultaneously aimed to understand the connection between them. However, single fluorescent tools for simultaneously visualizing LDs and lysosomes were rarely reported and they may be faced to poor water solubility or high cytotoxicity. Herein, we designed and synthesized a novel 1, 8-naphthalimide-based fluorescent monomer which can target to lysosomes and LDs simultaneously. The fluorescent monomer was applied to copolymerize with a hydrophilic material PEGMA300 by reversible addition-fragmentation chain transfer polymerization (RAFT) for construction of fluorescent amphiphilic block copolymer Poly (Nap-Lyso-MMA- co -PEGMA300 ) for the first time, which exhibited good water solubility and photostability, large Stokes shift (almost 130 nm), good selectivity, low cytotoxicity, and wide pH stability. Furthermore, it was sensitive to the solvent polarity and lipo-solubility. We successfully achieved a series of bio-imaging applications such as cell imaging, lysosome-LDs dual-locating imaging. These results indicated that the fluorescent copolymer possessed the remarkable bio-membrane penetration, lysosomes-targeting with the Pearson's Correlation of 0.832443, LDs-specificity with the Pearson's Correlation of 0.938595. Interestingly, fluorescent polymer could locate in dual-organelles simultaneously with different fluorescence signal, which could distinguish by the dot-fluorescence in LDs and the sheet-fluorescence in Lysosomes, accompanied by the brighter fluorescence in LDs than in Lysosomes. Based on these good properties as mentioned above, we expect the synthetic fluorescent polyacrylate could serve as a promised candidate to understand the interplay between lysosomes and LDs for promoting progress in biomedical fields.